2020
DOI: 10.1002/tcr.202000158
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Approaches to the Development of Artificial Transcription Factors Based on Pyrrole‐Imidazole Polyamides

Abstract: To maintain the functions of living organisms, cells have developed complex gene regulatory networks. Transcription factors have a central role in spatiotemporal control of gene expression and this has motivated us to develop artificial transcription factors that mimic their function. We found that three functions could be mimicked by applying our chemical approaches: i) efficient delivery into organelles that contain target DNA, ii) specific DNA binding to the target genomic region, and iii) regulation of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
(149 reference statements)
1
10
0
Order By: Relevance
“…We hypothesized that inhibition of chimeric TFE3 transcriptional activity, which blocks the proposed acquisition of chemoresistance through the PRCC–TFE3/HMOX1 axis, might be an effective therapeutic strategy for TFE3‐RCC. PI polyamides are synthetic oligomers that can recognize specific DNA sequences by designing the PI pairs to the target site of the genome 28,29 . Using the PI pairs targeting RUNX‐binding sequences conjugated to the nitrogen mustard alkylating agent, chlorambucil (Chb), we previously showed that Chb can efficiently inhibit the recruitment of RUNX family transcription factors to their binding sites and demonstrated their therapeutic potential for acute myeloid leukemia (AML) cells 21 …”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that inhibition of chimeric TFE3 transcriptional activity, which blocks the proposed acquisition of chemoresistance through the PRCC–TFE3/HMOX1 axis, might be an effective therapeutic strategy for TFE3‐RCC. PI polyamides are synthetic oligomers that can recognize specific DNA sequences by designing the PI pairs to the target site of the genome 28,29 . Using the PI pairs targeting RUNX‐binding sequences conjugated to the nitrogen mustard alkylating agent, chlorambucil (Chb), we previously showed that Chb can efficiently inhibit the recruitment of RUNX family transcription factors to their binding sites and demonstrated their therapeutic potential for acute myeloid leukemia (AML) cells 21 …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a PI polyamide was also reported to localize in mitochondria by binding to a lipophilic cation mitochondrial permeable protein (MPP), and the targeted ND6 gene expression was successfully inhibited by binding inhibition at the transcription factor mitochondrial transcription factor A (TFAM) binding sites for ND6 gene promotion 22 . Moreover, an alkylating MMP‐PIP of 8950A‐Chb, which targets a nonpathogenic mutation (m.8950G>A) in HeLa S3 cells, eliminated target mutated mtDNA, although the use of alkylating agent of chlorambucil may be limited depending on specific alkylation at the adenine sequence 69 . We also discovered that non‐alkylating PI polyamide‐TPP conjugates (PIP‐TPPs) induced sequence‐specific mitochondrial dysregulation.…”
Section: Pi Polyamides Can Target the Mitochondrial Genomementioning
confidence: 99%
“… 22 Moreover, an alkylating MMP‐PIP of 8950A‐Chb, which targets a nonpathogenic mutation (m.8950G>A) in HeLa S3 cells, eliminated target mutated mtDNA, although the use of alkylating agent of chlorambucil may be limited depending on specific alkylation at the adenine sequence. 69 We also discovered that non‐alkylating PI polyamide‐TPP conjugates (PIP‐TPPs) induced sequence‐specific mitochondrial dysregulation. As TPP had a lower molecular weight than MPP peptides and was widely used for mitochondrion‐targeting molecules and drug candidates, 36 , 68 we selected and synthesized PIP‐TPPs, which were found to permeate into cells without the aid of special drug delivery systems (DDS).…”
Section: Pi Polyamides Can Target the Mitochondrial Genomementioning
confidence: 99%
“…However, a more sensitive analytical method is desired. Pyrrole-imidazole polyamide, which is a groove binder, allows the molecular design of sequence-specific binding to DNA by changing the sequence of the constituent pyrroles and imidazoles (72). We used the reaction of Br U triggered by electron transfer to investigate the polyamide-binding sites on a DNA duplex (73,74).…”
Section: Reaction Of 5-halouracil In B-form Dna Induced By a Photoind...mentioning
confidence: 99%